P32. Histological evaluation of mesotheliomas - Vlacic, Gregor (Transl Lung Cancer Res, 2014)
BACKGROUND: Mesothelioma is the most frequent primary neoplasm affecting the pleura and still has a very grim prognosis. The classification is based on the histomorphological appearance and distinguishes epitheloid, sarcomatoid and biphasic variants with the epitheloid type having a longer overall survival compared to the other two. A new classification has been proposed by the international mesothelioma working group. It divides the epithelioid variant into subcategories based on the histological pattern, namely solid, acinar, adenomatoid, micropapillary, tubulopapillary, trabecular, small cell, clear cell, signet ring cell, adenoid cystic, deciduoid, rhabdoid and pleomorphic. The sarcomatoid variant was subclassified as conventional (spindle cell), desmoplastic, lymphohistiocytoid and with heterologous differentiation. Our goal was to review the cases from three institutions applying the new classification and to assess possible criteria. METHODS: We reviewed the HE slides of 200 consecutive mesotheliomas. There were resection specimens, needle biopsies (blind and CT guided) and thoracoscopic biopsies from three institutions using the proposed classification (University Clinic of Golnik, Slovenia and Institute of Pathology, University of Zagreb School of Medicine and University Hospital Centre Zagreb, Croatia). RESULTS: We evaluated 179 cases as having epitheloid morphology (89.5%), 11 as biphasic (5.5%) and 10 as sarcomatoid (5%). Among the epitheloid mesotheliomas 59 were solid (29.5% considering all 200 cases), 24 acinar (12%), 18 tubulopapillary (9%), 14 adenomatoid (7%), nine micropapillary (4.5%), eight pleomorphic (4%), five trabecular (2.5%). The other patterns (clear cell, small cell, rhabdoid, decidous, signet ring cell, adenoid cystic) were rarely identified but together made up for 42 cases (21%). CONCLUSIONS: While reviewing the cases we encountered several diagnostic issues especially regarding patterns that share many features (solid and deciduoid, acinar and adenomatoid etc.) as well as subclassifying sarcomatoid variants. Another issue is the relative small number of tumor cells in needle biopsies which makes it harder to evaluate and firmly categorize the pattern in one of the proposed options. It would be useful to review the classification through interobserver and possibly even intraobserver variability given the subjective bias of this task.